Prarancangan Pabrik Metanol Dari Batubara Dengan Proses Gasifikasi Kapasitas Produksi 100.000 Ton/Tahun - Asokawati, Anggie Fatimah, Kusmiyati, S.T., M.T., Ph.D, M. Mujiburohman, S.T., M.T., Ph.D (2016)
Methanol plant with raw material from gas synthesis of coal capacity 100.000 ton/years operated 330 days per years. Methanol manufactured process using fixed bed reactor. Reaction on fixed bed reactor occur gas phase, and exothermic, with operation condition non adiabatic at temperatur 2000C and pressure 48 atm. This industry include kind of high risk because operate above atmospheric pressure. Coal demand as much as 12.626,262 kg/hours. The product is methanol as much as 9.097,242 kg/hours. Utility process include water supply from river (Kapuas, West Kalimantan), steam supply from boiler with diesel fuel, electricity needs supplied by PLN and 1 generator set 500 kW as stand-by with diesel fuel. This plant is established in Rasau, West Kalimantan, Indonesia, on 2025, with land area 28.575 m2 and employees 159 people. The results of the economic analysis of the obtained methanol plant pradesign fixed capital investment (FCI) of Rp 149.619.846.137 and working capital (WC) Rp 88.799.730.394. Feasibility analysis results obtained from the return on investment (ROI) before tax after tax 44,82% and 31,37%. Pay Out Time (POT) before and after- tax 1,82 and 2,42 of years. Break Even Point (BEP) 42,05%, Shut Down Point (SDP) of 22,65% and a Discounted Cash Flow (DCF) of 30,28%. The results of the economic analysis concluded that the methanol plant from coal with gasification process capacity of 100.000 ton/year is feasible to set.